Masculine Heroine; a Study on the Phenomenon of Commodity Fetishism in the Hunger Games by Suzanne Collins - Hana Farida (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
Women are often treated as commodities which in the production process accept normalization to increase their selling value. Through her novel, Collins presented Katniss as a subject of objectification in order to create a discourse on commodity fethisism through media. The objectification also included the alteration of her image as a woman. This research was conducted with the aim of revealing how the image of a woman was constructed to display a particular ideology and how Katniss's deviation from objectification actually turned her out to be another kind of commodity fethisim object. By utilizing theoretical concepts of Marx's commodity fethisism and Butler's gender construction, this study focused on the discussion of the construction of a woman's image which was attached to the main character of the novel, Katniss Everdeen, and then objectified, and also the discourse of commodity fethisism that arised along with it. In the process of analysis, this research used descriptive analytical methods which described the objectification and commodification of Katniss as a woman as an attempt of normalization to confirm a power discourse in patriarchal capitalist society. Furthermore, the later phenomenon of commodity fethisism that was present because of its failure thus showed the collapse of the patriarchal discourse imposed on Katniss as a woman, but at the same time gave rise to other patriarchal ideologies.Keywords: commodity fethisism, women's image, objectification and normalization, gender construction.